Hepatocyte Toll-like receptors contribute to the hepcidin inflammatory response to pathogens and pathogen-derived ligands - Bonitz, Katharina; Colucci, Silvia; Qiu, Ruiyue; Altamura, Sandro; Sparla, Richard; Müdder, Katja; Zimmermann, Stefan; Hentze, Matthias W.; Muckenthaler, Martina; Marques, Oriana (HemaSphere, 2025)
Iron restriction is a critical pathomechanism underlying the Anemia of Inflammation and an innate immune response limiting the replication of extracellular pathogens. During infections, innate immune cells detect pathogen-associated molecular patterns (PAMPs) and produce proinflammatory cytokines. Among these, interleukin (IL)-6 is detected by hepatocytes, where it activates the production of the iron-regulated hormone hepcidin that inhibits iron export from macrophages. Consequently, macrophages accumulate iron and hypoferremia (low plasma iron) develops. Whether Toll-like receptors (TLRs) expressed on hepatocytes directly recognize PAMPs and contribute to hepcidin upregulation is still an open question. Stimulation of primary murine hepatocytes with a panel of PAMPs targeting TLRs 1-9 revealed that the TLR5 ligand flagellin and the TLR2:TLR6 ligand FSL1 upregulated hepcidin. Hepcidin was also induced upon treatment with heat-killed Staphylococcus aureus (HKSA) and Brucella abortus (HKBA). The hepcidin response to flagellin, FSL1, HKSA, and HKBA started at an early time point, was independent of autocrine regulation by IL-6, and occurred through the TLR-mitogen-activated protein kinase (MAPK) axis. By analyzing a macrophage:hepatocyte co-culture, we additionally show that the hepcidin response was dependent on TLR2:TLR6 expression in hepatocytes and independent of macrophage cytokine secretion. Ex vivo liver perfusion of mice with FSL1 and HKSA further revealed that PAMPs and pathogens can pass the sinusoidal barrier and reach hepatocytes to cause hepcidin upregulation in a TLR2:TLR6-dependent manner. We conclude that hepatocytes can directly recognize PAMPs and pathogens and promote hepcidin upregulation in a macrophage and cytokine-independent manner. This positions hepatocytes in the spotlight as potential direct drivers of iron restriction.
In der Verantwortlichkeitsangabe ist der Nachname der Autorin Katja Müdder als Mudder angegeben
Online veröffentlicht: 3. April 2025
Gesehen am 26.06.2025